Management of streaming processes in organizational, technological and economic systems of building industry companies in order to increase their competitiveness in unstable market - Arutiunian, I. (Ways to Improve Construction Efficiency, 2019)
The article reflects the approaches to solving the actual task of managing streaming processes, which make it possible to timely organize incoming processes for interrupted implementation of building processes, taking into account the economic possibilities of logistical tools. In order to implement these approaches, it’s necessary to consider and apply modern models of logistics concepts for managing streaming processes in organizational, technological and economic systems of building industry companies in unstable market.